THE RELATIONSHIP BETWEEN HIGH GLYCEMIC INDEX DIET AND MUSCULOSKELETAL DISORDERS - Adinda, Adinda; Legiran; Arwan Bin Laeto; Ayeshah Augusta Rosdah; Eka Febri Zulissetiana; Kamalia Layal (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Musculoskeletal disorders include acute and chronic conditions affecting the muscles, bones, joints, and supporting structures in the neck, back, and limbs, posing significant challenges across all age groups. Approximately 30% of cases occur in adolescents and individuals in their productive years, not just in the elderly. These disorders lead to substantial socioeconomic and health burdens. Previous research indicates that dietary patterns play a critical role in the onset and progression of these conditions. A persistent high-glycemic index (GI) diet is associated with systemic inflammation, metabolic dysregulation, and musculoskeletal health. This study aims to provide a comprehensive review of existing literature to summarize and identify the potential relationship between high-GI diets and the prevalence of musculoskeletal disorders (MSDs). Articles were collected using search engines such as PubMed, Medscape, and ScienceDirect, focusing on publications from 2013 to 2024. The findings emphasize the importance of dietary interventions as modifiable risk factors for preventing and managing musculoskeletal disorders, particularly in at-risk populations. Further studies are needed to develop dietary strategies to reduce the global burden of musculoskeletal disorders effectively.